(untitled) - Joanna Channell (Oxford, 1994)
The book shows how English provides its speakers with a great variety of ways of being vague. It applies principles of pragmatics to the analysis of vague expressions, describing both the linguistic forms and the pragmatic consequences of their use
Keywords: english language - spoken english,language and languages - study and teaching - research